MANAJEMEN KERJASAMA KEMITRAAN SMK KAUTSAR WAY SULAN DENGAN DUNIA USAHA DAN DUNIA INDUSTRI UNTUK MENINGKATKAN MUTU LULUSAN - Timbul Santoso; Septuri; Heru Juabdin Sada (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Management of partnerships with the business and industrial world (DUDI) is one strategy to strengthen the link and match between the world of education and the world of work, so that vocational school graduates have competencies that match the needs of industry. The revitalization of vocational schools is a priority program of the government in order to produce graduates who have competencies that match the needs of the world of. The government's attention to the revitalization of vocational schools is outlined in Presidential Instruction No. 9 of 2016, which was refined by the issuance of Ministerial Regulation No. 165/M/2021 as an effort to develop the quality of human resources in vocational schools through the Center of Excellence vocational school program, which emphasizes the importance of strategic partnerships with DUDI. This study aims to describe how cooperation management is implemented at Kautsar Way Sulan Vocational School in establishing relationships with the business and industrial world. The cooperation programs carried out include curriculum synchronization, teacher training, field work practice (PKL), competency certification, and workforce distribution. The research method used a qualitative descriptive approach with data collection techniques through interviews, observations, and documentation, while data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results of the study show that partnership management is carried out by building fostered partners that are strengthened by Islamic principles such as deliberation, mutual assistance in goodness, and communication based on qoulan sadida, baligha, ma'rufa, karima, layyinan, and masyura. Cooperation is evaluated periodically to ensure the effectiveness of the program and as a basis for developing cooperation in the following year.